Improved catalytic performance and molecular insight for lipoxygenase from Enterovibrio norvegicus via directed evolution - Zhang, Bingjie; Chi, Huibing; Shen, Juan; Tao, Yang; Lu, Zhaoxin; Lu, Fengxia; Zhu, Ping (Frontiers in Bioengineering and Biotechnology, 2023)
Lipoxygenase (LOX) holds significant promise for food and pharmaceutical industries. However, albeit its application has been hampered by low catalytic activity and suboptimal thermostability. To address the drawbacks, a directed evolution strategy was explored to enhance the catalytic activity and thermostability of LOX from Enterovibrio norvegicus (EnLOX) for the first time. After two rounds of error-prone polymerase chain reaction (error-prone PCR) and one generations of sequential DNA shuffling, all of four different mutants showed a significant increase in the specific activity of EnLOX, ranging from 132.07±9.34 to 330.17±18.54 U/mg. Among these mutants, D95E/T99A/A121H/S142N/N444W/S613G (EAHNWG) exhibited the highest specific activity, which was 8.25-fold higher than the wild-type enzyme (WT). Meanwhile, the catalytic efficiency (Kcat/Km) of EAHNWG was also improved, which was 13.61±1.67 s -1 •μM -1 , in comparison to that of WT (4.83±0.38 s -1 •μM -1 ). In addition, mutant EAHNWG had a satisfied thermostability with the t1/2,50 °C value of 6.44±0.24 h, which was 0.4 h longer than that of the WT. Furthermore, the molecular dynamics simulation and structural analysis demonstrated that the reduction of hydrogen bonds number, the enhancement of hydrophobic interactions in the catalytic pocket, and the improvement of flexibility of the lid domain facilitated structural stability and the strength of substrate binding capacity for improved thermal stability and catalytic efficiency of mutant LOX after directed evolution. Overall, these results could provide the guidance for further enzymatic modification of LOX with high catalytic performance for industrial application.